Love, crisis processes, couple breakups and dis-love. Lines of reflection from the social approach based on Latin American music "plancha" - Loáciga, Carlos Vargas (2019)
Romantic love is one of the most interesting and complex processes, bothsocially and individually. Defining it in one way is even more complex.However, we have all experienced it in one way or another. We find it in allsocial spheres and in all stages of life, generating sensations that are possiblyunique and particular. Nobody knows how or at what moment love hascome to us, but we experience it, and we accumulate experiences that havegiven us great satisfactions. But how do we fall in love? How did we learn todifferentiate what was love with respect to any other sensation or emotion?This article is based on the premise that nobody has taught us to love, and oursocial processes have allowed us to build fantasies and myths about falling inlove, which mark us in each of the romantic experiences of a couple, at sucha level that, When difficulties arise during the relationship, we do not knowhow to resolve them, because we think that eternal love will be perfect. Inview of this, the objective of this article is to give continuity to the reflectionsmade in the article "Love, falling in love and the body" (2017), but focusingon the processes of crisis, ruptures and dis-love that we all go through, takingreference the Latin American music “plancha”.